Methodology for assessing the quality of work on removing trees and shrubs - Platonov Alexey; Platonova Marina (BIO Web of Conferences)
When carrying out work on the proper maintenance of a number of linear infrastructure facilities, the problem of assessing the quality of work performed to remove unwanted trees and shrubs from the territories of these facilities remains relevant. Given that the quality of these works is often assessed only by considering the regulatory and technical documents accompanying the work, the purpose of the research was to develop a methodology for assessing the quality and effectiveness of work to remove unwanted trees and shrubs from the territories of linear infrastructure facilities with the justification of the criteria for this assessment. The developed methodology was based on the principle of analyzing data on the normative and actual degree of overgrowth of the studied territories, which is implemented by carrying out their taxation survey. The methodology developed by the authors of the study provides a program and implementation of a set of organizational and technological issues to identify the characteristics of unwanted vegetation, and also determines the scope and content of the scale of criteria for assessing the quality of measures taken to remove unwanted vegetation from the territories of linear infrastructure facilities.